2014
DOI: 10.7899/jce-13-25
|View full text |Cite
|
Sign up to set email alerts
|

The learning style preferences of chiropractic students: A cross-sectional study

Abstract: Objective : The aims of our study were to measure the learning style preferences of chiropractic students and to assess whether they differ across the 5 years of chiropractic study. Methods : A total of 407 (41.4% females) full-degree, undergraduate, and postgraduate students enrolled in an Australian chiropractic program agreed to participate in a cross-sectional survey comprised of basic demographic information and the Visual, Aural, Read/Write, Kinesthetic (VARK) questionnaire, which identifies learning pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 22 publications
4
24
1
Order By: Relevance
“…The outcome of this study also indicated that both (multimodal and unimodal) presentations did not change over the course of study [30]. The study by Turner et al also identified the similar result regarding learning preferences of pediatric residents using VARK and the Kolb Learning Style Inventory.…”
Section: Review and Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The outcome of this study also indicated that both (multimodal and unimodal) presentations did not change over the course of study [30]. The study by Turner et al also identified the similar result regarding learning preferences of pediatric residents using VARK and the Kolb Learning Style Inventory.…”
Section: Review and Discussionsupporting
confidence: 75%
“…While the study done by Whillier et al showed no significant difference between unimodal and multimodal learning styles from first year to fifth year. But there was significant difference in preferences for visual and read/write type of learning style as the age increases [30]. These results were just opposite as we compare the findings of the study done by Murphy et al (among undergraduate dental student) and by El Tantawi (among postgraduate dental students).…”
Section: Learning Style and Agecontrasting
confidence: 69%
See 1 more Smart Citation
“…The study by Whillier showed that chiropractic students had a preference for the kinaesthetic learning style, which did not change over the course of the study. (12) Liew found a majority of the students had a unimodal (kinesthetic) learning style. (18) The study by Turner showed that the majority of paediatric residents were kinaesthetic.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors infl uence a student's learning style including the gender, (8)(9)(10)(11) age, (12) geographical background, (13) and educational major (14) among other factors. Th e level of education is also considered to be one factor that aff ects the learning style.…”
Section: Introductionmentioning
confidence: 99%